2020
DOI: 10.1007/s11914-020-00616-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulators of Mesenchymal Stem/Stromal Cell Lineage Determination

Abstract: Purpose of Review Although many signalling pathways have been discovered to be essential in mesenchymal stem/stromal (MSC) differentiation, it has become increasingly clear in recent years that epigenetic regulation of gene transcription is a vital component of lineage determination, encompassing diet, lifestyle and parental influences on bone, fat and cartilage development. Recent Findings This review discusses how specific enzymes that modify histone methylation and acetylation or DNA methylation orchestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…Runx2 binds to and activates the Sp7 promoter ( Yoshida et al, 2012 ), indicating that Runx2 is an upstream transcription factor during osteogenesis, but that this differentiation process requires the expression of both master regulators ( Long, 2012 ). In recent years, several groups have demonstrated that changes in chromatin structure and expression of the Runx2 and Sp7 genes are epigenetically-controlled ( Yang et al, 2013 , 2015 ; Tai et al, 2014 ; Dudakovic et al, 2015 ; Rojas et al, 2015 , 2019 ; Zhang et al, 2015 ; Aguilar et al, 2016 , 2020 ; Park-Min, 2016 ; Zhou et al, 2016 ; Sepulveda et al, 2017a ; Cakouros and Gronthos, 2020 ; Figure 1 ).…”
Section: Epigenetic Control Of the Expression Of Master Regulators Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Runx2 binds to and activates the Sp7 promoter ( Yoshida et al, 2012 ), indicating that Runx2 is an upstream transcription factor during osteogenesis, but that this differentiation process requires the expression of both master regulators ( Long, 2012 ). In recent years, several groups have demonstrated that changes in chromatin structure and expression of the Runx2 and Sp7 genes are epigenetically-controlled ( Yang et al, 2013 , 2015 ; Tai et al, 2014 ; Dudakovic et al, 2015 ; Rojas et al, 2015 , 2019 ; Zhang et al, 2015 ; Aguilar et al, 2016 , 2020 ; Park-Min, 2016 ; Zhou et al, 2016 ; Sepulveda et al, 2017a ; Cakouros and Gronthos, 2020 ; Figure 1 ).…”
Section: Epigenetic Control Of the Expression Of Master Regulators Ofmentioning
confidence: 99%
“…Findings from several teams revealed that regulating the repressive mark H3K27me3 represents an important step during the differentiation of MSCs toward osteoblasts. It was demonstrated that the activity of the H3K27 demethylases Utx/Kdm6a and Jmjd3/Kdm6b is critical for erasing this mark from the promoter of the Runx2 and Sp7 genes ( Figure 1 ) and hence to induce their expression during osteogenesis ( Ye et al, 2012 ; Hemming et al, 2014 ; Rojas et al, 2015 ; Park-Min, 2016 ; Sepulveda et al, 2017b ; Cakouros and Gronthos, 2020 ; Sen et al, 2020 ). Additionally, an increased activity of the PRC2 complex that “writes” the H3K27me3 mark, can significantly limit the ability of MSCs to engage osteogenic differentiation ( Wei et al, 2010 ).…”
Section: Epigenetic Control Of the Expression Of Master Regulators Ofmentioning
confidence: 99%
“…Growing evidence shows that MSC differentiation is influenced by several epigenetic processes/factors, including histone methylation and acetylation, DNA methylation [ 23 ], non-coding RNA molecules, such as long non-coding RNAs (lncRNA) [ 24 ], and miRNAs [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is tightly linked to aging via epigenetic changes in mesenchymal stem cells (MSCs) [ 163 ]. Physiologically, the Osterix promoter was shown to entail enriched levels of H3Ac/H3K4me3 and reduced levels of H3K9me3/H3K27me3, inducing the differentiation of MSCs into osteoblasts to mediate skeletal tissue homeostasis [ 163 , 164 ]. Among the key transcription factors for osteogenesis are HOX and RUNX2, both of which are hypermethylated in aged MSCs [ 165 ].…”
Section: Epigenetics Of Aging and Aging-related Diseasesmentioning
confidence: 99%
“…It was shown in human bone marrow stromal cells (BMSCs) that in osteoporosis the number of clonogenic BMSCs was reduced, corresponding to decreased levels of Tet1 and Tet2 , factors, which are able to erase DNA methylation. During normal osteogenesis, TET1 and TET2 levels were enhanced with an increased binding to the Osterix promoter [ 163 , 167 ]. Yang et al detected an osteopenic phenotype and decreased Runx2 expression in Tet1 −/− Prx1 cre Tet2 fl/fl mice.…”
Section: Epigenetics Of Aging and Aging-related Diseasesmentioning
confidence: 99%